SISTEM KUBUR PENGHUNI GUA KIDANG, BLORA - Nurani, Indah Asikin; Koesbardiati, Toetik; Murti, Delta Bayu (BRIN, 2014)
Three human remains (Homo sapiens) have been found in Gua Kidang (Kidang cave). This brings a new contribution to the burial system that is already known among prehistoric man in Holocene era. The third human remain has not been fully unearthed yet. But the anatomical position of the body indicates a primary burial. Although the three human remains werw found in different layer, but they laid closed to each other. This condition leads to the questions, i.e. was Gua Kidang occupied by people with different racial and cultural background? Did the people do different burial system? The result shows that teeth can be used to determine dental wear. This paper will explain the way of life of the human remains viewed from â€œthe religiousâ€ aspects. In addition, based on the stratigraphic position of the study Geoarchaeology.